Hydrothermal Production of Furfural from Corn Husk Biomass Using an AlCl₃–HCl Catalytic System - Novia Kirana Maharani; Desi Karnisa; Dita Ariyanti; Meka Saima Perdani (Universitas Negeri Medan, 2026)
Hydrothermal production of furfural from corn husk biomass was investigated using an AlCl₃–HCl–H₂SO₄ catalytic system. Hydrothermal treatment was carried out in a Teflon-lined reactor at 120 °C for 6 h with a solid-to-liquid ratio of 1:20 (g/mL). The catalytic system consisted of 200 mg AlCl₃, 330 µL HCl, and 110 µL H₂SO₄. Structural and chemical changes during the conversion process were analyzed using FTIR and HPLC. The results indicated partial degradation of lignocellulosic components, particularly hemicellulose, which promoted furfural formation during hydrothermal conversion. Quantitative analysis showed that furfural yield increased from 0.30% without catalyst addition to 2.37% with the AlCl₃-containing catalytic system, indicating the catalytic contribution toward hydrolysis and dehydration reactions. In addition, comparison of solvent systems showed that dimethyl carbonate (DMC) produced higher furfural yield (2.37%) than dichloromethane (DCM) (1.03%) under similar hydrothermal conditions, suggesting that solvent selection influenced furfural stabilization and conversion efficiency. Although the obtained furfural yield remained lower than values reported for optimized acid-catalyzed systems, the findings demonstrate the potential of corn husk biomass as a renewable feedstock for furfural production and provide preliminary insight into catalyst-assisted hydrothermal conversion.